PENINGKATAN PEMBELAJARAN PASSING BAWAH DALAM PERMAINAN BOLA VOLI DENGAN METODE BERMAIN MENGGUNAKAN PAPAN PANTUL PADA SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA KRISTEN ABDI WACANA KOTA PONTIANAK - Yaya Sukarya; Fatirul Wa’asil; Samsu Nurfalah (Journal Physical Education, Health and Recreation, 2018)
The problem in this research is the ability and skill of passing down technique on the game of volleyball in the students of class VIII Christian High School Abdi Wacana Pontianak is still low. Action Research This class aims to improve lower passing technique skills on volleyball games at grade VIII students Christian Junior High School Abdi Wacana Pontianak through play activities on boards. The subjects of the study were VIII students of the academic year 2014/2015 at Christian Junior High School Abdi Wacana Pontianak, amounting to 24 students. Technique of data collecting by doing direct observation and measurement technique. Data analysis techniques are qualitative and quantitative analysis. The result of the research shows that by using the bounce play method can increase the learning result. The improvement can be seen especially from: a) the learning plan every cycle is very good, b) the implementation of each cycle there is improvement based on the previous reflection, c) the learning result of the learners increased. Initial data of students who reached KKM 33.33%, in the first cycle increased to 50%, and cycle II reached 87.5%.